Alpha-2 Adrenergic Receptors and Attention—Deficit/Hyperactivity Disorder - Bidwell, L. Cinnamon (2010)
Pharmacological management of attention-deficit hyperactivity disorder (ADHD) has expanded beyond stimulant medications to include alpha 2 adrenergic agonists. These agents exert their actions through presynaptic stimulation and likely involve facilitation of both dopamine and noradrenaline neurotransmission, which are both thought to play critical roles in the pathophysiology of ADHD. Further, frontostratial dysfunction giving rise to neuropsychological weaknesses has been well-established in patients with ADHD and may explain how alpha 2 agents exert their beneficial effects. In the following review, we consider relevant neurobiological underpinnings of ADHD with respect to why alpha 2 agents may be effective in treating this condition. We also review new formulations of alpha 2 agonists, emerging data on their use in ADHD, and implications for clinical practice. Integrating knowledge of pathphysiological mechanisms and mechanisms of drug action may inform our medication choices and facilitate treatment of ADHD and related disorders.